BARROS, José D’Assunção. Teoria da História Vol. I. Princípios e conceitos. Petrópolis/RJ. Editora Vozes, 3ª Ed., 2013, 319 p. - SALGUEIRO, EDUARDO DE MELO (Outros Tempos: Pesquisa em Foco - História, 2013)
Boa leitura!